Thermoelectric properties of tetrathiotetracene iodide crystals: modeling and experiment - Casian, A.I.; Sanduleac, I.I. (Springer US, 2014)
A more complete physical model for nanostructured crystals of tetrathiotetracene-iodide that takes into account the interaction of carriers with the neighboring one-dimensional (1D) conductive chains and also the scattering on impurities and defects is presented. For simplicity, the 2D approximation is applied. It is shown that this model describes very well the temperature dependencies of electrical conductivity in the temperature interval between 180 and 300 K, and of the Seebeck coefficient between 50 and 300 K, the highest temperature for which the measurements were reported. For lower temperatures, it is necessary to also consider the fluctuations of dielectric phase that appear before the metal–dielectric transition. It is found that the predictions made in the 1D approximation are valid only if the crystal purity is not very high, and the electrical conductivity is limited up to ∼3.5×106Ω−1m−1 and the thermoelectric figure of merit up to ZT∼4.